2020
DOI: 10.1016/j.bbrc.2019.11.089
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy regulator Atg9 is degraded by the proteasome

Abstract: Autophagy is a highly conserved biological process essential to protein, cellular and organismal homeostasis. As autophagy plays a critical role in cellular responses to various external and internal stimuli, it is important to understand the mechanism underlying autophagy regulation. Here, we monitor the stability of 17 key autophagy factors in the yeast S. cerevisiae and show that Atg9 and Atg14 are degraded under normal growth conditions. Whereas Atg14 is regulated by both the proteasome and autophagy, Atg9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…This fits with recent evidence showing that UPS activity, rather than inhibition, promotes autophagy both by fostering the nuclear translocation of TFEB, and remarkably, by degrading mTOR itself, leading to its downregulation and detachment from the lysosomes [111]. In baseline conditions the turnover of the transmembrane autophagy protein Atg9 is also carried out by the UPS, while this is impeded upon autophagy-inducing stimuli such as starvation or rapamycin treatment [112]. Likewise, upon ubiquitination by the ubiquitin-activating enzyme UBA6 and the ubiquitin-conjugating enzyme/ubiquitin ligase BIRC6, LC3-II is targeted for UPS degradation [115,116].…”
Section: Emerging Mechanisms Underlying Autophagy and Proteasome Crossupporting
confidence: 90%
See 1 more Smart Citation
“…This fits with recent evidence showing that UPS activity, rather than inhibition, promotes autophagy both by fostering the nuclear translocation of TFEB, and remarkably, by degrading mTOR itself, leading to its downregulation and detachment from the lysosomes [111]. In baseline conditions the turnover of the transmembrane autophagy protein Atg9 is also carried out by the UPS, while this is impeded upon autophagy-inducing stimuli such as starvation or rapamycin treatment [112]. Likewise, upon ubiquitination by the ubiquitin-activating enzyme UBA6 and the ubiquitin-conjugating enzyme/ubiquitin ligase BIRC6, LC3-II is targeted for UPS degradation [115,116].…”
Section: Emerging Mechanisms Underlying Autophagy and Proteasome Crossupporting
confidence: 90%
“…In this functional setting, the merging between UPS and autophagy is defined as "proteaphagy". This is in line with studies indicating a reciprocal regulation between the two cell-clearing systems, with UPS behaving as a sentinel in sensing and regulating autophagy, and vice versa [68,[108][109][110][111][112][113]. In detail, UPS regulates the duration and amplitude of the autophagy response by controlling the stability of Unc-51 like autophagy activating kinase (ULK1)/Atg1 complex as well as mTOR and transcription factor EB (TFEB) kinases [108][109][110].…”
Section: Emerging Mechanisms Underlying Autophagy and Proteasome Crossupporting
confidence: 86%
“…Recently, it was found that two other Atg proteins are regulated by ubiquitination: Atg14 is degraded by the ubiquitin-proteasome system as a means to modulate autophagy activity [ 23 ], and Atg9 is degraded by the proteasome under normal conditions but stabilized upon starvation and rapamycin treatment [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The impaired UPS and autophagy defects also result in reduced clearance of tau tangles present in brains of AD patients, impairing the synapsis and cognition in patients [363]. Recent studies revealed important roles of UPS in regulating Atg9 availability, which in turn regulates autophagy progression [364]. In general, the nutrient status of a cell regulates UPS-dependent regulation of several cellular proteins and transcription factors that drive cell fate.…”
Section: Proteostasis Failure In Admentioning
confidence: 99%